2022
DOI: 10.1126/science.abg3679
|View full text |Cite
|
Sign up to set email alerts
|

Hippo signaling instructs ectopic but not normal organ growth

Abstract: The Hippo signaling pathway is widely considered a master regulator of organ growth because of the prominent overgrowth phenotypes caused by experimental manipulation of its activity. Contrary to this model, we show here that removing Hippo transcriptional output did not impair the ability of the mouse liver and Drosophila eyes to grow to their normal size. Moreover, the transcriptional activity of the Hippo pathway effectors Yap/Taz/Yki did not correlate with cell proliferation, and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 80 publications
2
48
0
1
Order By: Relevance
“…As shown in Figure 3H, Y_1 cells shared an expression profile similar to that of the VPE and INT. This similarity to peripodial membrane cells of the VPE is in line with previous work which suggests that Yki is primarily active in cells of the peripodial membrane 39 . Importantly, the Y_1 transcriptional profile most closely resembled wild type interommatidial cells INT, but showed no similarity to anterior cell populations.…”
Section: Ectopic Expression Of Constitutively Activated Yki In Rbf Mu...supporting
confidence: 91%
“…As shown in Figure 3H, Y_1 cells shared an expression profile similar to that of the VPE and INT. This similarity to peripodial membrane cells of the VPE is in line with previous work which suggests that Yki is primarily active in cells of the peripodial membrane 39 . Importantly, the Y_1 transcriptional profile most closely resembled wild type interommatidial cells INT, but showed no similarity to anterior cell populations.…”
Section: Ectopic Expression Of Constitutively Activated Yki In Rbf Mu...supporting
confidence: 91%
“…Similarly, we mapped an Yki signature gene set composed of 52 genes to our data (18) (Supplemental Table 3) and found that the scrib -/-Yki S168A clones exhibit higher expression level of Yki target genes in comparison with GFP-cells (Figure 1J'). The scrib -/-N Act clones express higher level of the enhancer of split gene complex, which are well-known Notch signaling targets (19) (Figure 1K').…”
Section: Resultsmentioning
confidence: 91%
“…In the absence of Yki, Sd binds to repressors and is thought to reduce expression of target genes (Guo et al, 2013; Koontz et al, 2013). Loss of sd causes the loss of both its activator and repressor functions and, in many contexts, results in relatively minor changes in tissue size (Goulev et al, 2008; Wu et al, 2008; Zhang et al, 2008; Kowalczyk et al, 2022). Although sd null clones fail to grow in the PE of the eye disc (Kowalczyk et al, 2022), and Yki/Sd-mediated cell proliferation promotes stretch-induced growth of the egg follicle epithelium (Borreguero-Muñoz et al, 2019), the frequent lack of a strong growth phenotype upon sd loss has placed into question whether the Hippo pathway plays a significant role in size regulation during normal development (Kowalczyk et al, 2022).…”
Section: Resultsmentioning
confidence: 99%